2012
DOI: 10.1371/journal.pone.0034292
|View full text |Cite
|
Sign up to set email alerts
|

Longer Leukocyte Telomere Length Is Associated with Smaller Hippocampal Volume among Non-Demented APOE ε3/ε3 Subjects

Abstract: Telomere length shortens with cellular division, and leukocyte telomere length is used as a marker for systemic telomere length. The hippocampus hosts adult neurogenesis and is an important structure for episodic memory, and carriers of the apolipoprotein E ε4 allele exhibit higher hippocampal atrophy rates and differing telomere dynamics compared with non-carriers. The authors investigated whether leukocyte telomere length was associated with hippocampal volume in 57 cognitively intact subjects (29 ε3/ε3 carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
3
31
4
1
Order By: Relevance
“…With telomerase activation, telomerase elongates telomeres in certain cells, including brain cells, in response to cell damage (Greider and Blackburn, 1985; Mattson, 2000). Consistent with this, some studies have reported telomerase activation and longer hippocampal telomeres in AD brain tissue than in non-demented tissue (Thomas et al, 2008; Wikgren et al, 2012a). ALT is a homologous recombination-based mechanism that uses a DNA template to preserve telomere length, and results in very long telomeres (Bryan et al, 1995) and ALT-associated promyelocytic leukemia bodies (Muntoni and Reddel, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…With telomerase activation, telomerase elongates telomeres in certain cells, including brain cells, in response to cell damage (Greider and Blackburn, 1985; Mattson, 2000). Consistent with this, some studies have reported telomerase activation and longer hippocampal telomeres in AD brain tissue than in non-demented tissue (Thomas et al, 2008; Wikgren et al, 2012a). ALT is a homologous recombination-based mechanism that uses a DNA template to preserve telomere length, and results in very long telomeres (Bryan et al, 1995) and ALT-associated promyelocytic leukemia bodies (Muntoni and Reddel, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…Wikgren et al found that, while shorter LTL was correlated with greater subcortical atrophy and more white matter hyper-intensities (Wikgren et al, 2013), shorter LTL was correlated with larger hippocampal volume. This was found in non-demented apolipoprotein E ε3/ε3 carriers, but not in non-demented apolipoprotein E ε4 carriers (Wikgren et al, 2012a). The authors interpreted their finding in the non-demented apolipoprotein E ε3/ε3 carriers as being consistent with greater overall cellular proliferation in leukocytes as well as in the hippocampus, which would lead to relatively shorter LTL due to more frequent mitoses but relatively larger hippocampal volume due to more neurogenesis in the dentate gyrus.…”
Section: Relationship Of Peripheral Cell Aging Markers To the Brainmentioning
confidence: 81%
“…Methodological differences between studies, as well as many studies with small sample sizes, make conclusions difficult to draw. Although the reasons for the discrepancies between studies are unknown, possibilities include different subject demographics (e.g., age, gender, race, socioeconomic status, history of childhood adversity (O'Donovan et al, 2011a; Price et al, 2013)), different study designs, differences in duration or severity of the investigated illness (Wolkowitz et al, 2011a), different specimen processing and assay protocols (Aviv et al, 2006; Montpetit et al, 2014; Nieratschker et al, 2013) and, importantly, differences in moderators of LTL and PBMC basal TA that are often not assessed, e.g., genetic risk-alleles (Armanios and Blackburn, 2012; Codd et al 2013), including ApoE status (Jacobs et al, 2013; Takata et al, 2012; Wikgren et al, 2012a), cognitive threat appraisal (O'Donovan et al, 2012), pessimistic outlook (O'Donovan et al, 2009), arousal and regulatory system activation (Epel, 2009) and stress resiliency factors (Puterman et al, 2013). For example, recent data suggest that “high risk” genetic polymorphisms in the serotonin and dopamine systems may interact with early life adversity to affect adult LTL (Mitchell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако интересно, что более длинные теломерные участки соответствуют сниженному объему гиппокампа и наличию нарушений запоминания. Ис-следователи связывают это с затруднениями пролифе-рации клеток при нейрогенезе, который определяет эффективность формирования памяти [18]. Пациенты с минимальными когнитивными нарушениями имеют достоверно меньшую длину теломер по сравнению со здоровыми людьми, что объясняют процессами старе-ния и нейродегенерации.…”
Section: актуальные вопросы патофизиологииunclassified